Evaluation of New Film Based on Chitosan/Gold Nanocomposites on Antibacterial Property and Wound-Healing Efficacy. (29th July 2020) - Wang, Kai; Wang, Haosheng; Pan, Su; Fu, Chuan; Chang, YuXin; Li, Hongru; Yang, Xiaoyu; Qi, Zhiping
Abstract : Chitosan (CS) is a natural polymer with applications in wound restorations and coatings for artificial implants. However, the lack of antimicrobial activity restricts its further application. Thus, the purpose of this study is to prepare CS/AuNPs film by adding gold nanoparticles (AuNPs) to modify chitosan. Through transmission electron microscopy, we found that the presence of CS can effectively prevent the agglomeration of nanoparticles. Furthermore, through the CCK experiment, we found that AuNPs at a certain concentration can improve the adhesion and proliferation of cells, which has also been proved in animal experiments, including gross appearance, histological observations, and immunofluorescence staining. Such findings support the feasibility of using the film as a promising candidate for tissue engineering of skin in a near future.